Gender-Dimorphic Impact of PXR Genotype and Haplotype on Hepatotoxicity During Antituberculosis Treatment. Issue 24 (June 2015) - Wang, Jann Yuan; Tsai, Ching Hui; Lee, Yungling Leo; Lee, Li Na; Hsu, Chia Lin; Chang, Hsiu Ching; Chen, Jong Ming; Hsu, Cheng An; Yu, Chong Jen; Yang, Pan Chyr; Naranbhai., Vivek
<x xml:space="preserve">Abstract</x> Abstract Women have a higher risk of drug-induced hepatotoxicity during antituberculosis treatment (HATT) than men. We hypothesized that single nucleotide polymorphism (SNP) genotype and derived haplotype of pregnane X receptor (PXR) gene, which could regulate the expression of phase I enzyme cytochrome P450 (CYP) 3A4, had a sex-specific influence on the risk of HATT. Six SNPs of the PXR gene were sequenced. Genotypes and haplotypes of the PXR SNPs, and other potential risk factors for HATT were compared between pulmonary TB patients with and those without HATT. HATT was defined as an increase in serum transaminase level >3 times the upper limit of normal (ULN) with symptoms, or >5 times ULN without symptoms. We performed the study in a derivation and a validation cohort. Among the 355 patients with pulmonary TB in the derivation cohort, 70 (19.7%) developed HATT. Logistic regression analysis revealed the risk of HATT increased in female genotype AA at rs2461823 (OR: 6.87 [2.55–18.52]) and decreased in female genotype AA at rs7643645 (OR: 0.14 [0.02–1.02]) of PXR gene. Haplotype analysis showed that female h001101 (OR: 2.30 [1.22–4.32]) and female h000110 (OR: 2.25 [1.08–4.69]) haplotype were associated with increased HATT risk. The identified predictors were also significantly associated with female HATT risk among the 182 patients in the validation cohort. Two PXR SNP genotypes and 2 haplotypes influenced the risk of HATT only in females. The PXR SNP showed a sex-specific impact that contributed to an increased HATT risk in females.